Analisis Kinerja Keuangan Pemerintah Daerah Kabupatn Sikka Tahun 2011-2015 - THERECA FEBRYANI GOBAPUSPITA (Jurnal Ilmiah Mahasiswa FEB, 2017)
The implementation of regional autonomy through fiscal decentralization scheme has not been able to exploit regional income that, in the long run, can support the success of the region in implementing the regional autonomy. With regard to such a problem, this research aims at examining the financial performance of the regional government in Sikka regency through ratio analysis towards the regional finance (financial independence ratio, effectiveness ratio, efficiency ratio, compatibility ratio, and growth ratio). This descriptive quantitative research applies document study for the data collection method. The data of this study were obtained through documentation method. The results of the analysis illustrate that the financial independence of Sikka Regency is still low, and it is categorized into instructive relationship pattern. Meanwhile, its own- source revenue is very effective, and its regional tax is efficient. However, the regional expenditure shows lack of compatibility in terms of its direct and indirect expenditures towards the total expenditure of the region. In addition, the regional income and expenditure growths also persistently fluctuate.Keywords: Fiscal Decentralization, Regional Government Financial Ratio